2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27319
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Software Testing to CS Curriculum Using WRESTT-CyLE

Abstract: Dr. Yujian Fu is an associate professor of computer science department at Alabama A&M University. Her research interests fall in formal verification of cyber physical systems, behavioral analysis of mobile security, software architecture and design analysis of safety-critical and mission-critical systems. Her projects are supported by NSF, Air Force and DoD. She have several publications regarding to the research and educational projects. Prof. Nelson Barnes Jr, Alabama A&M UniversityProf. Barnes has performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We discuss the importance of verification/validation in the STE curriculum as one of the main topics in computer science & Engineering discipline. Graham/Harrold [21,18] highlight Tehseen et al the integration of the development process, testing process and these are discussed in the STE curriculum. We also discussed ACM different curricula versions 2013/2008/2006 and 2003 these all curricula give a good perception to evaluate and develop the courses taught in Computer science & engineering disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We discuss the importance of verification/validation in the STE curriculum as one of the main topics in computer science & Engineering discipline. Graham/Harrold [21,18] highlight Tehseen et al the integration of the development process, testing process and these are discussed in the STE curriculum. We also discussed ACM different curricula versions 2013/2008/2006 and 2003 these all curricula give a good perception to evaluate and develop the courses taught in Computer science & engineering disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Pech et al [48] suggested the collaboration tool for supplementary training and practices in the software testing area. Similarly, in the research published by Fu and Clarke [72], authors suggested a cyberlearning environment that could be used in parallel with traditional software testing lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Each learning unit in STEM-CyLE is composed of learning content, practice, quiz and assessment. Currently, STEM-CyLE covers programming language learning units, cyber security, other than the major component of software testing [1,2,35]. STEM-CyLE is a cyber-learning environment that uses assorted learning and engagement strategies including collaborative learning [32], problem-based learning, gamification [3,35,36], and social interaction.…”
Section: Feedbacks Of Stem-cylementioning
confidence: 99%
“…STEM-CyLE is a cyber-learning environment that uses assorted learning and engagement strategies including collaborative learning [32], problem-based learning, gamification [3,35,36], and social interaction. The fusion of gamification, social interaction, and collaborative learning in STEM-CyLE helps students explore and discuss topics in software programming content [37], software tools, and a variety of other areas [1,4,34]. A number of testing tools were introduced during the course period to support understanding of the knowledge units in the textbook.…”
Section: Feedbacks Of Stem-cylementioning
confidence: 99%